The impact of silo storage on the fatigue and cracking resistance of asphalt mixes. (4th April 2022) - Elkashef, Mohamed; Harvey, John; Jones, David; Jiao, Liya
Highlights: Silo storage has a notable effect on the mix cracking and fatigue properties. The SCB and IDEAL-CT tests are highly influenced by mix aging. The FI and CTindex show good correlation for the tested mixes. The FI correlates with the displacement at 75 percent peak load. The FI and CTindex do not correlate with the fatigue life from the flexural beam test. Abstract: During production, hot mix asphalt plants can store mixes in silos for a few hours before they get transported to the job site. Additional aging and possible blending between RAP and virgin binders take place inside the silo which affect mix properties. This study addresses the impact of silo storage on mix fatigue and cracking performance. The flexural beam test has been widely established as a representative fatigue test, however due to its complexity, it is difficult to implement as a quality control test. The semi-circular bending test (SCB) and the indirect tensile asphalt cracking test (IDEAL-CT) are simple and quick tests that are currently being used by some state agencies to assess the cracking resistance of asphalt mixes. The ability of SCB and IDEAL-CT to predict fatigue-related cracking as compared to flexural beam testing is also investigated in this study. Four plant-produced mixes were collected before and after silo storage, and tested using flexural beam, SCB, and IDEAL-CT. It was noted that the SCB and IDEAL-CT are highly influenced by the mix stiffness, and the cracking resistance was reduced considerably with silo storage. This finding has important implications when using either of these tests for construction quality control and assurance. It was concluded that the flexibility index (FI) from the SCB and the cracking tensile index (CTindex ) from the IDEAL-CT did not provide a direct measure of the fatigue performance as compared to the flexural beam test.